Unravelling the impact of the chromobox proteins in human cancers - Shabana Noreen; Nicla Simonelli; Rosaria Benedetti; Vincenzo Carafa; Michele Grieco; Concetta Ambrosino; Carmela Dell’Aversana; Angela Nebbioso; Mariarosaria Conte; Nunzio Del Gaudio; Lucia Altucci (Cell Death and Disease)
Abstract Chromobox (CBX) proteins play a crucial role in regulating epigenetic processes. They are extensively involved in various biological processes, including embryonic development, stem cell maintenance, cell proliferation and apoptosis control. The disruption and malfunction of CBXs in cancer typically results in the interference or abnormal activation of developmental pathways, which facilitate the onset, growth, and advancement of cancer. This review initially introduces the physiological properties and functions of the CBXs. Subsequently, it examines the involvement of CBXs in different cancer types. Cancer hallmarks driven by CBXs are mediated through multiple mechanisms, including changes in gene expression patterns, epigenetic dysregulation of chromatin control, disruption of intracellular signaling and alterations in cell metabolism. The study also highlights novel potential anticancer therapeutics targeting CBXs in cancer. In this review we provide novel perspectives and a solid foundation for future investigations on CBXs as promising therapeutic targets for cancer treatment.